PENGARUH SLUDGE LIMBAH KELAPA SAWIT DAN PUPUK NPKMg (15:15:6:4) DALAM MEDIA TANAM ULTISOL TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI MAIN NURSERY - Pramana, Nanda Dwi; Amri, Al Ikhsan; ', Ardian (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The research aimed to determine the effect of interaction giving palm oil waste sludge and NPKMg (15:15:6:4) fertilizer on Ultisol and get the best treatment to the growth of palm oil (Elaeis guineensis Jacq.) seedlings in main nursery. The research was conducted at the experimental field of the Faculty of Agriculture, University of Riau. This research was conducted from March to July 2015. The research used Completely Randomized Design factorial that consisting of two factors. The first factor is palm oil waste sludge (S) consists of 4 levels. The second factor is the NPKMg (15:15:6:4) fertilizer (P) consists of 3 levels. Both these factors resulted in 12 treatment combinations, each combination made 3 replications, so that there are 36 experimental units. Each experimental unit consisted of 2 plants, so the total crop was 72 plants. Parameters measured were the increase seedling height, the number of leaves increase, the increase hump diameter, leaf area, root volume and dry weight. Data were analyzed by analysis of variance and further tested using Duncan`s New Multiple Range Test at the level of 5%.The results of the research showed that there is interaction between giving application palm oil waste sludge and NPKMg fertilizer on increase of seed hump diameter dan seed dry weight. Combination treatment of sludge dose with 100 g/plant and NPKMg fertilizer with 10,5 g/plant is the best treatment that can be recommended to get the growth palm oil seedling in main nursery on Ultisol. Â Keywords: palm oil, growth, Ultisol, palm oil waste sludge, NPKMg fertilizer